Cooperative and competitive school climate: their impact on sense of belonging across cultures - Ooi, Shi Xin; Cortina, Kai S. (Frontiers in Education, 2023)
The role of sense of belonging within an educational context has been well-documented. Previous studies on belongingness using OECD-PISA data showed that the degree to which students feel a sense of belongingness to their school varies across countries. The current study extents the prior findings by analyzing the relationship between the sense of belonging and perceived competitiveness and cooperation in schools using the 2018 PISA cycle, including data from 76 countries. Perceived cooperation across all countries and aggregated on the country level was significantly and positively correlated with belongingness. Belongingness regressed on perceived competitiveness and perceived cooperativity results in both variables being significant predictors in the expected directions. Together, the two climate variables explained 18.8% of the variance on belongingness between countries. Thus, there is robust cross-cultural evidence that sense of belongingness is negatively affected by a competitive and positively by a cooperative classroom climate.